Integrating Adopter Categories into Adoption Trends among Coconut Growers in Coimbatore District, Tamil Nadu - Devi, M Nirmala; Karthikeyan, C; Mohanraj, V; Tayang, Weijimlu (Indian Journal of Extension Education, 2024)
Coconut, a versatile tropical fruit, holds significant importance globally, with India being a major contributor to its cultivation. In recent years, innovative practices in coconut cultivation have gained momentum by enhancing yield, quality, and resilience. However, the adoption of coconut production technologies among small-scale farmers remained slow. Therefore this research study aimed to shed light on the dynamic adoption behaviour of coconut growers’ in the Coimbatore district of Tamil Nadu, India. The study comprised of 120 farmers, who were selected through proportionate random sampling from two villages in the Coimbatore district. Based on the adoption of the latest technology available in coconut production, coconut grower’s adoption level was measured using percentage analysis. Findings revealed that the largest adopter category was innovators. The deviation was attributed to the uniqueness of the recommended varieties and coconut tonic adoption, regional cultural influences, and targeted awareness campaigns. The study highlights the importance of tailored awareness campaigns and incentives aimed at promoting innovation adoption among farmers to enhance production. With enhanced adoption of these practices, the coconut farming sector in the Coimbatore district and beyond can experience improved productivity, economic growth, and sustainable development.
Keywords: Adoption; Adopter categories; Innovators; Coconut tonic; Coconut varieties